ANALYSIS OF THE MOBILE PAYMENT ONLINE SYSTEM APPLICATION OF THE PALOPO CITY REGIONAL GOVERNMENT BASED ON USER SATISFACTION - Pakkaja, Ryan Alghazali; Luthfi, Ahmad; Haryono, Kholid (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2024)
The electronic-based government system is now the best step for every region, and it certainly has a mission to educate the area regarding governance. Efforts have been made by the government to meet citizens' expectations for easier access to public services, which is the primary form of E-Government. Currently, the implementation of the existing E-Government concept can also be a new breakthrough in improving information technology-based services. One is the Mobile Payment Online System Application, built directly by the Palopo City Government through its strategic partner, Bank Sulselbar. However, special attention must still be given to implementing this application, especially to the system itself, which is less effective. Additionally, many individuals still take actions that are not in accordance with the procedures, as evidenced by the fraud committed by application users. This research uses qualitative methods that provide descriptive data results, describing the data occurring in the field. The data generated using quasi-experimental methods will be calculated using the same Likert scale. This research shows that the Mobile Payment Online System Application still needs to be socialized again to the users of this application and requires application development in terms of tool updates and system updates. This can be seen from the respondents' responses through the questionnaire results table and suggestions from these respondents. Thus, the Mobile Payment Online System Application is still ineffective for implementation in Palopo City.